New Concepts of Endoplasmic Reticulum Function in the Heart: Programmed to Conserve - Doroudgar, Shirin (2012)
Secreted and transmembrane proteins play critical roles in myocardial health and disease. Studies in non-myocytes have shown that the peri-nuclear ER is the site for synthesis, folding and quality control of most secreted and transmembrane proteins, as well as a nexus of a signal transduction system, the ER stress response, that informs the cell about the status of ER protein folding. Moreover, the dynamic physical and functional association of the ER with mitochondria has emerged as a key site of integrating ER function with mitochondrial metabolism, but is only just beginning to be understood in the myocardium. Although a great deal is known about roles played by the sarcoplasmic reticulum (SR) in contractile calcium handling in the heart, little is known about the relative locations and functions of the peri-nuclear ER and the SR in terms of secreted and membrane protein synthesis and folding. In this review we will explore the current state of knowledge of the location of secreted and membrane protein synthesis, folding, and quality control machinery in cardiac myocytes, as well as our understanding of the functional consequences of ER stress and the unfolded protein response in the heart in terms of protein synthesis, cell growth, and metabolic regulation.